Strategic Management of Educators’ Work Ethic Development in Al-Muhajir Foundation, Lumajang - Nurjannah, Riska; Mu'is, Abdul; Umam, Khotibul (MANAGIERE: Journal of Islamic Educational Management, 2024)
This study analyzes the strategic management of educators’ and staff work ethic development at Al-Muhajir Foundation, Randuagung Lumajang. The institution’s quality is strongly influenced by human resources, particularly leadership in designing and executing strategies. The research focuses on three aspects: (1) strategic planning, (2) implementation, and (3) evaluation. Using a qualitative case study, data were obtained through interviews, observations, and documentation, then analyzed with Miles and Huberman’s interactive model, ensuring validity with source and technique triangulation. Findings show that strategic planning involves SWOT analysis, vision–mission formulation, and goal setting. Implementation is carried out through training, self-development, internships, and comparative studies, while evaluation includes weekly and monthly meetings, religious studies, and annual assessments (munaqosah). These strategies collectively foster work ethic, professionalism, and organizational commitment, contributing to the foundation’s educational quality improvement. Penelitian ini mengkaji manajemen strategis pengembangan etos kerja pendidik dan tenaga kependidikan di Yayasan Al-Muhajir Randuagung Lumajang. Mutu pendidikan sangat bergantung pada kualitas sumber daya manusia, khususnya kepemimpinan dalam merumuskan dan melaksanakan strategi. Fokus penelitian meliputi: (1) perencanaan, (2) implementasi, dan (3) evaluasi strategi. Pendekatan kualitatif dengan studi kasus digunakan, dengan pengumpulan data melalui wawancara, observasi, dan dokumentasi. Analisis dilakukan menggunakan model interaktif Miles dan Huberman, dengan keabsahan data dijamin melalui triangulasi sumber dan teknik. Hasil menunjukkan bahwa perencanaan mencakup analisis SWOT, visi–misi, dan penetapan tujuan; implementasi dilakukan melalui pelatihan, pengembangan diri, magang, dan studi banding; sedangkan evaluasi melalui rapat, kajian keagamaan, dan munaqosah tahunan. Secara keseluruhan, strategi ini memperkuat etos kerja, profesionalisme, dan komitmen organisasi, sehingga mendukung peningkatan mutu pendidikan yayasan.